Meningkatkan Pemahaman Nilai – Nilai Pancasila dengan Pembelajaran Kooperatif Metode STAD pada Siswa SMA Negeri 6 Kaur Bengkulu - Tarmizi, Tarmizi (Attractive : Innovative Education Journal, 2020)
Pancasila values ​​among students are increasingly degraded by globalization. It need an effective learning model to overcome it’s problem. Through this article the author gives test Student Teams-Achievement Division (STAD) Method Cooperative Learning to improve students' understanding of Pancasila values. The researcher used a two-cycle class action research approach to solve the problem of poor understanding of Pancasila values. Each cycle consists of planning, implementation, observation and evaluation, as well as analysis and reflection. There were 25 students as research sample from Senior High School (SMA) 6 Kaur Bengkulu. The data collection is the result of observations and questionnaires. The data analyzed by using quantitative and qualitative descriptive techniques. The results showed that there was an increase in understanding of Pancasila values. In cycle 1, from an initial score of 81.52 to 96.2, it was seen that students gave responses by asking questions. In cycle 2, from a score of 96.2 to 110.6, here students begin to be able to analyze and respond positively to the learning methods used. Keywords: Pancasila Value, STAD Method, Cooperative Learning